Assessing and Mapping the Impact of Tourism and Changing Climatic Conditions in Himalayan Region of Pakistan - YASIN, Asma; SHAHZAD, Laila; HAYYAT, Muhammad Umar; GHAFOOR, Gul Zareen; SAEED, Salar; SHARIF, Faiza; RAIZ, Umair; SALEEM, Muhammad Bilal (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023, 2023)
Khaghan and Naran Valley of Pakistan are popular tourist mountainous region and face direct impacts of environmental degradation in past years. The current study aims to map the impacts of tourism on the local community and how it has affected the environmental settings. Mixed method approach was utilized including questionnaire survey; meteorological records, focused group interviews and mapping the land cover changes using satellite imagery. Meteorological data shows anomaly in rainfall patterns and extreme temperature which can be considered as climatic pressures on fragile environment. Spearman’s correlation showed that environmental degradation was linked with increased tourism activities in the region. Normalized Difference Vegetation Index (NDVI) shows an increasing trend of land degradation by the conversion of forested areas into settlements. Considering the significant magnitude of degradation over the last decade, appropriate and urgent actions are needed to address the growing demand of the tourism sector.